OVERVIEW OF THE SCIENTIFIC BASIS AND WEANING ABILITY IN LARVAE CULTURE FOR CLOWNFISH (Amphiprion spp.) - Trang, Tran Thi Le; Sawatpera, Saowapa (Vietnam Journal of Marine Science and Technology, 2012)
An overview of histological studies on the development of the digestive system and tests for determining the optimum age for weaning on clownfish larvae has critical importance in order to establish optimal feeding regimes for their culture. Before hatching clownfish larvae possess a differentiated alimentary tract, liver and pancreas with absorptive and digestive capabilities; therefore clownfish larvae readily accept rotifers after hatching. However, gastric glands in the stomach strongly develop about 2 weeks of age depending on species and culture condition. The time of feeding on Artemia and artificial food for some clownfish larvae can begin from 7-10 and 14 day of ages, respectively. Key words: clownfish, histological studies, digestive system, weaning.